Pulmonary vein isolation with the radiofrequency balloon catheter: a single centre prospective study. Issue 3 (4th February 2023) - Del Monte, Alvise; Almorad, Alexandre; Pannone, Luigi; Della Rocca, Domenico Giovanni; Bisignani, Antonio; Monaco, Cinzia; Mouram, Sahar; Ramak, Robbert; Gauthey, Anaïs; Overeinder, Ingrid; Bala, Gezim; Sorgente, Antonio; et al.
Abstract: Aims: The multielectrode radiofrequency balloon catheter (RFB) has been developed to achieve safe and effective pulmonary vein isolation (PVI) for atrial fibrillation (AF) ablation. This single-centre study aimed to evaluate the midterm clinical outcome and predictors of single-shot PVI with the novel RFB. Methods and results: All consecutive patients with symptomatic paroxysmal or persistent AF undergoing first-time PVI with the RFB were prospectively included. Clinical and procedural parameters were systematically collected. The primary safety endpoint was defined as any major periprocedural complications. The primary efficacy endpoint consisted of freedom from any atrial tachyarrhythmias (ATas) lasting >30 s during the follow-up after a 3-month blanking period. Persistent single-shot PVI was defined as PVI achieved with a single RFB application without acute reconnection. A total of 104 consecutive patients (mean age 64.3 ± 11.4 years, 56.7% males) were included. 15 patients (14.4%) presented with persistent AF. The procedure time was 59.0 min with a dwell time of 20.0 min. One major complication occurred in one patient. At a mean follow-up of 10.1 ± 5.3 months, freedom from ATas was 82.9%. ATas occurred in 14 patients, 11/69 patients (15.9%) with paroxysmal AF and 3/13 (23.1%) with persistent AF. The best cut-offs to predict persistent single-shot PVI were impedance drop >19.2 Ω [area under the receiver operator characteristic curve (AUC) 0.74] and temperature rise >11.1° C (AUC 0.77). Conclusion: In a large cohort of patients undergoing PVI with the RFB, the complication rate was 1%. At a mid-term follow-up of 10.1 ± 5.3 months, freedom from ATas was 82.9%. Specific cut-offs of impedance drop and temperature rise may be useful to predict persistent single-shot isolation. Graphical Abstract: Graphical Abstract